Stereotactic Iodine-125 Brachytherapy for Low-Grade Glioma Treatment: A Monte Carlo study - Shahrzad Valizadeh; Elham Saeedzadeh; Alireza Zali; Hasanali Nedaei; Saeed Zare Ganjaroodi (International Clinical Neuroscience Journal, 2022)
Background: Stereotactic brachytherapy is an appropriate method that has been used for brain tumors and metastases treatment for more than 40 years for many patients in the world. Also, iodine-125 brachytherapy has been utilized in brain tumors for interstitial brachytherapy treatment since 1979. Even though the physical and biological features make these implants particularly attractive for minimal invasive treatment, the main goal of this paper is to evaluate the I-125 seed time and dose reached to brain glioma tumors of different sizes for treatment using Monte Carlo modeling. Methods: In this paper, Monte Carlo simulation has been applied by the Gate code with 20 (MBq) activity for an iodine seed design for low-grade glioma tumors treatment. Dosimetry features of this source were defined by the updated TG-43U1 recommendations. The absorbed dose distribution around the seed was calculated using the Gate code in liquid water. Result: The ideal condition for brachytherapy is for tumors smaller than 4 cm. With a larger tumor size, the absorption dose at the border of tumor and healthy tissue will be decreased and the implantation time for seeds will increase. Conclusion: Placing an iodine-125 source inside the tumor is not sufficient because of the non-uniform dose distribution in the tumor and the length of treatment time. Using four iodine-125 sources eliminates the tumor, and also, a uniform dose distribution is created in the tumor and the implantation time will be reduced, respectively.